2019
DOI: 10.1021/acs.orglett.8b03767
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III)/Copper(II)-Cocatalyzed Cycloaddition/[3,3]-Rearrangement/N–O Bond Cleavage To Prepare Polysubstituted Pyrrolizines from N-Vinyl-α,β-Unsaturated Nitrones and Activated Alkynes

Abstract: An efficient one-pot synthesis of polysubstituted pyrrolizines from N-vinyl-α,β-unsaturated nitrones and activated alkynes through iron­(III)/copper­(II)-cocatalyzed [3 + 2] cycloaddition/[3,3]-rearrangement and sequential N–O bond cleavage was developed. The reaction first underwent [3 + 2] cycloaddition and [3,3]-rearrangement to afford nine-membered N-heterocycles, and then a controlled N–O bond cleavage of nine-membered rings by iron­(III)/copper­(II) cocatalysts delivered pyrrolizine scaffolds. A kinetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 69 publications
0
10
0
2
Order By: Relevance
“…During the studies on the N ‐vinyl nitrones and their cycloadditions in our group, we recently developed a novel strategy for the highly diastereoselective synthesis of nine‐membered ring scaffolds though a [3+2] cycloaddition and sequential [3,3]‐rearrangement cascade strategy from N ‐vinyl‐α,β‐unsaturated ketonitrones and various electrophiles, including arynes, isocyanates, and methylenecyclopropanes [12] . In 2019, we developed a iron/copper‐cocatalyzed [3+2] cycloaddition, [3,3] rearrangement and N−O bond cleavage from N ‐vinyl‐α,β‐unsaturated ketonitrones and activated alkynes to prepare a series of polysubstituted pyrrolizines in good yields (Scheme 1‐A) [13] . Further studies showed that a kinetic resolution of nine‐membered ring compounds was the first time achieved to afford chiral nine‐membered ring and chiral pyrrolizines by using copper(II) acetate combined with chiral PyBox ligand, however, the kinetic resolution efficiency was low and the enantioselectivity of the recovered nine‐membered ring compounds and pyrrolizines was up to only 83% ee and 53% ee, respectively.…”
Section: Figurementioning
confidence: 99%
“…During the studies on the N ‐vinyl nitrones and their cycloadditions in our group, we recently developed a novel strategy for the highly diastereoselective synthesis of nine‐membered ring scaffolds though a [3+2] cycloaddition and sequential [3,3]‐rearrangement cascade strategy from N ‐vinyl‐α,β‐unsaturated ketonitrones and various electrophiles, including arynes, isocyanates, and methylenecyclopropanes [12] . In 2019, we developed a iron/copper‐cocatalyzed [3+2] cycloaddition, [3,3] rearrangement and N−O bond cleavage from N ‐vinyl‐α,β‐unsaturated ketonitrones and activated alkynes to prepare a series of polysubstituted pyrrolizines in good yields (Scheme 1‐A) [13] . Further studies showed that a kinetic resolution of nine‐membered ring compounds was the first time achieved to afford chiral nine‐membered ring and chiral pyrrolizines by using copper(II) acetate combined with chiral PyBox ligand, however, the kinetic resolution efficiency was low and the enantioselectivity of the recovered nine‐membered ring compounds and pyrrolizines was up to only 83% ee and 53% ee, respectively.…”
Section: Figurementioning
confidence: 99%
“…2019 年, 莫冬亮课题组 [44] 以 N-烯基-α,β-不饱和硝 同时, 研究发现将醋酸铜与手性 PyBox 配体结合, 实现了氮杂九元环化合物的动力学拆分, 回收的氮杂九 元环化合物的 ee 值达 83%, 稠环吡咯化合物的 ee 值为 52%, 拆分效率 S 值为 8. 为手性氮杂九元环化合物的合 成提供了新方法(Eq.…”
Section: N-烯基-αβ-不饱和硝酮构建吡咯化合物unclassified
“…Quinoxalin-2(1H)-ones are prevalent nitrogen-heterocyclic units [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] in a broad range of pharmaceutically and biologically active compounds [19,20]. As a consequence, the development of novel synthetic protocols for the facile diversification of quinoxalin-2(1H)-one has been actively explored over the past few years [21].…”
mentioning
confidence: 99%